2021
DOI: 10.3389/fneur.2021.700269
|View full text |Cite
|
Sign up to set email alerts
|

Progression in Neuroimaging of Normal Pressure Hydrocephalus

Abstract: Normal-pressure hydrocephalus is a clinical syndrome that mainly targets the elderly population. It features dementia, impaired walking, and the malfunction of sphincters. The rapid identification and large-scale screening of patients with normal-pressure hydrocephalus (NPH) are of great significance as surgical interventions can greatly improve or even reverse the symptoms. This review aims to summarize the traditional parameters used to diagnose NPH and the emerging progression in neuroimaging of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(38 reference statements)
0
3
0
3
Order By: Relevance
“…An Evans index of more than 0.31 highly suggests the presence of hydrocephalus. 5 More recently, disproportionately enlarged subarachnoid-space hydrocephalus, visualized as narrowed medial subarachnoid spaces at the high convexity on coronal MRI, has been described as another indicator of NPH, which takes into account the unevenly enlarged ventricles and sylvian fissures compared with the extent of background cerebral atrophy. 5 Normal pressure hydrocephalus gradually progresses over time.…”
Section: Discussionmentioning
confidence: 99%
“…An Evans index of more than 0.31 highly suggests the presence of hydrocephalus. 5 More recently, disproportionately enlarged subarachnoid-space hydrocephalus, visualized as narrowed medial subarachnoid spaces at the high convexity on coronal MRI, has been described as another indicator of NPH, which takes into account the unevenly enlarged ventricles and sylvian fissures compared with the extent of background cerebral atrophy. 5 Normal pressure hydrocephalus gradually progresses over time.…”
Section: Discussionmentioning
confidence: 99%
“…Un indice d’Evans supérieur à 0,31 est fortement indicateur d’une hydrocéphalie 5 . Plus récemment, une hydrocéphalie disproportionnée de l’espace sous-arachnoïdien, qui se manifeste par un rétrécissement de l’espace sous-arachnoïdien médial au niveau de la convexité supérieure à l’IRM coronale, a été décrite comme un autre indicateur de l’HPN qui tient compte de l’hypertrophie inégale des ventricules et des sillons de Sylvius par rapport au degré d’atrophie des tissus cérébraux avoisinants 5 .…”
Section: Discussionunclassified
“…L'indice d'Evans est fortement indiqué comme indicateur de la ventriculomégalie, définie par le rapport entre la largeur maximale de la corne frontale du ventricule latéral divisée par la largeur maximale de la cavité du crâne, mesurées sur la même coupe axiale. Un indice d'Evans supérieur à 0,31 est fortement indicateur d'une hydrocéphalie 5 . Plus récemment, une hydrocéphalie disproportionnée de l'espace sous-arachnoïdien, qui se manifeste par un rétrécissement de l'espace sousarachnoïdien médial au niveau de la convexité supérieure à l'IRM coronale, a été décrite comme un autre indicateur de l'HPN qui tient compte de l'hypertrophie inégale des ventricules et des sillons de Sylvius par rapport au degré d'atrophie des tissus cérébraux avoisinants 5 Des complications surviennent dans plus du tiers des cas de dérivation.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Other imaging modalities include PET scan, which has proven useful in diagnosing NPH. In a retrospective study, Townley et al found that patients with iNPH had significant regional hypometabolism in the dorsal striatum involving the caudate and putamen bilaterally compared with healthy controls and patients with other types of dementia [39].…”
Section: Wernicke-korsakoff Syndromementioning
confidence: 99%